2022
DOI: 10.3389/fphar.2022.950457
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutics against neurological disorders: Natural products-based drugs

Abstract: Neurodegenerative disorders, which are defined by the breakdown of neurons over time, are affecting an increasing number of people. Stroke, Alzheimer's, Parkinson's, Multiple Sclerosis, Migraine, and Amyotrophic Lateral Sclerosis are just a few examples of brain disorders that have no cure. Besides, there is a huge demand for drugs that can cure the diseases mentioned above because the majority of the medications we use to treat them only alleviate diseases. Different neurological disorders have responded sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…[17] Till now, many agents of natural origin with robust antiinflammatory and antioxidant properties have been identified to exhibit beneficial effects in PD. [18,19] Therefore, it is under great urgency to develop more natural drugs to mitigate oxidative stress and neuroinflammation, which will help counteract dopaminergic neurodegeneration and alleviate PD progression.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Till now, many agents of natural origin with robust antiinflammatory and antioxidant properties have been identified to exhibit beneficial effects in PD. [18,19] Therefore, it is under great urgency to develop more natural drugs to mitigate oxidative stress and neuroinflammation, which will help counteract dopaminergic neurodegeneration and alleviate PD progression.…”
Section: Introductionmentioning
confidence: 99%
“…Only in the USA and Europe, the annual cost of treating mental disorders is USD 1.7 trillion [1]. More than 50 million and 322 million individuals suffer from epilepsy and depression, respectively [2]. Multiple investigations have indicated that anxiety and depression might simultaneously occur [3].…”
Section: Introductionmentioning
confidence: 99%
“…Neurological disorders (NDs) are increasingly prevalent and represent the leading cause of disability-adjusted life years [ 1 ]. They account for over 6% of the global disease burden [ 2 ], are the second most common cause of death worldwide with nine million deaths annually, and are exacerbated by severe health disparities.…”
Section: Introductionmentioning
confidence: 99%